Perawatan Tubuh Tradisional Pra-Nikah Calon Pengantin pada Melayu di Desa Semuntai Kecamatan Mukok Kabupaten Sanggau - Putri, Monica Mandala; Musa, Dahniar Th.; Darmawan, Diaz Restu (Universitas Tanjungpura, 2024)
Bridal showers called Batangas are essential steps in an ethnic Malay wedding in Sanggau Regency. Batangas is a steam bath procession that aims to cleanse oneself so they are ready to carry out the wedding procession. This research focuses on the Batangas procession of prospective brides and grooms in the Malay community. This research uses qualitative ethnographic methods conducted in Semuntai Village. Foster and Anderson's theory is used as an analytical tool. This research found that betangan is a pre-wedding tradition carried out with a steam bath. This tradition has health values, such as a body that feels healthier and more confident on the wedding day.